2018
DOI: 10.1186/s13068-018-1146-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of bacteria for improving the lignocellulose biorefinery process: importance of pre-erosion

Abstract: BackgroundBiological pretreatment is an important alternative strategy for biorefining lignocellulose and has attracted increasing attention in recent years. However, current designs for this pretreatment mainly focus on using various white rot fungi, overlooking the bacteria. To the best of our knowledge, for the first time, we evaluated the potential contribution of bacteria to lignocellulose pretreatment, with and without a physicochemical process, based on the bacterial strain Pandoraea sp. B-6 (hereafter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 75 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…In addition, the yield of the reducing sugar increased from 10.19 g/l (TH21) to 26.28 g/l (120 ℃ for 4 h, TH24) with the prolongation of reaction time under 120 ℃. This is 3.74 and 11.40-fold higher than that of the untreated sample (84.70 mg/g, that is 2.12 g/l [17]). This phenomenon is attributed to the breakdown of the biomass recalcitrance structure.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…In addition, the yield of the reducing sugar increased from 10.19 g/l (TH21) to 26.28 g/l (120 ℃ for 4 h, TH24) with the prolongation of reaction time under 120 ℃. This is 3.74 and 11.40-fold higher than that of the untreated sample (84.70 mg/g, that is 2.12 g/l [17]). This phenomenon is attributed to the breakdown of the biomass recalcitrance structure.…”
Section: Introductionmentioning
confidence: 63%
“…The CS used in this study was found to consist of 34.9% of cellulose, 38.5% of hemicellulose, 13.9% of lignin, and 12.7% of other non-organic and organic components [17]. The mass loss of CS under the reaction condition of TH21 was 36.14%.…”
Section: Mass Loss Of the Csmentioning
confidence: 81%
See 1 more Smart Citation
“…With further researches, inherent enzymes and metabolic pathways involved in lignin degradation by these bacteria have been characterized, including enzymes/pathways catalyzing oxidative and hydroxylation reactions, depolymerizing phenolic and non-phenolic lignin polymers, demethylation reactions and opening the aromatic rings of lignin-based compounds [33, 4045]. Now, some of these bacteria have been used in treatment of sewages from pulp and paper industry, degradation heterogeneous compounds, and pretreatment of lignocellulosic biomass [4649]. In particular, among these isolates, some strains (e.g., Pseudomonas putida KT2440, Sphingobium sp.…”
Section: The Lignin-degrading Bacteria and Their Screening Methodsmentioning
confidence: 99%
“…In our previous studies, a new strategy involved a synergy of lignocelluloses pretreatment by THF-H 2 O and bacterial strain to enhance enzymatic hydrolysis was developed [24,25]. The result showed THF-H 2 O had a high lignin removal efficiency and retained a large amount of cellulose for sugar production.…”
Section: Introductionmentioning
confidence: 99%